2022
DOI: 10.1097/cce.0000000000000674
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Accuracy of Presepsis and Intrasepsis Characteristics for Prediction of Cardiovascular Events After a Sepsis Hospitalization

Abstract: OBJECTIVES: Sepsis survivors face increased risk for cardiovascular complications; however, the contribution of intrasepsis events to cardiovascular risk profiles is unclear. SETTING: Kaiser Permanente Northern California (KPNC) and Intermountain Healthcare (IH) integrated healthcare delivery systems. SUBJECTS: Sepsis survivors (2011–2017 [KPNC] and 2018–2020 [IH]) greater than or equal to 40 years old without prior cardiovascular disease. DESIGN: Data across KPNC and IH were harmonized and grouped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Our study builds upon previous research demonstrating the increased risk of subsequent cardiovascular disease in sepsis survivors (e.g., compared with nonsepsis survivors of a hospitalization) (18, 20–23, 45, 46). Our results are consistent with findings from recent cohort studies highlighting that an elevated troponin value, sepsis-specific variables, and presepsis characteristics were associated with subsequent cardiovascular events (24, 27, 47). Our study provides additional information on preexisting comorbidities, cardiovascular and sepsis-specific characteristics that are likely associated with subsequent cardiovascular disease and assessing the risk over a longer follow-up and using population-based data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study builds upon previous research demonstrating the increased risk of subsequent cardiovascular disease in sepsis survivors (e.g., compared with nonsepsis survivors of a hospitalization) (18, 20–23, 45, 46). Our results are consistent with findings from recent cohort studies highlighting that an elevated troponin value, sepsis-specific variables, and presepsis characteristics were associated with subsequent cardiovascular events (24, 27, 47). Our study provides additional information on preexisting comorbidities, cardiovascular and sepsis-specific characteristics that are likely associated with subsequent cardiovascular disease and assessing the risk over a longer follow-up and using population-based data.…”
Section: Discussionsupporting
confidence: 93%
“…However, the risk factors for these cardiovascular complications remain uncertain-and the extent to which subsequent cardiovascular events are due to classic pathways (e.g., baseline risk factors such as hypertension) or sepsis-related complications is unknown (24). Better understanding of associated risk factors could potentially help 1) generate hypothesis for translational research models and 2) identify subgroups of patients at low or high risk of cardiovascular disease (12,18,(25)(26)(27). This could in turn inform the enrichment of future trials evaluating potential preventative strategies (e.g., statin use after discharge) (28).…”
mentioning
confidence: 99%
“…Pre-existing diabetes represents a classic cardiovascular risk factor in the general population, whereas mounting evidence from observational studies show the increased risk of cardiovascular disease in sepsis survivors [ 14 16 , 27 , 51 53 ]. Furthermore, the potential role for diabetes as an independent risk factor for cardiovascular disease in adult sepsis survivors has also been recently highlighted [ 21 , 23 , 54 ]. Prior studies have shown how, among other baseline comorbidities and characteristics of the sepsis episode, pre-existing diabetes may be associated with a higher risk of cardiovascular disease following sepsis; however, these studies were not designed specifically to quantify the impact of diabetes and were undertaken mostly within a prediction framework [ 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a retrospective cohort study of patients ≥40 years old who survived a hospitalization for sepsis at 21 KPNC hospitals admitted between January 1, 2011 and September 30, 2017 with new‐onset AF. We previously described the cohort inclusion/exclusion criteria 8 . Briefly, AF was present on the cardiac rhythm flow sheet using a previously validated method that scans flowsheets to estimate time spent in certain heart rhythms 9 .…”
Section: Methodsmentioning
confidence: 99%